Immobilization of cyclodextringlucanotransferase from Bacillus maceranson bleached kenafbast micro-fibre - Ng, Lin Cieh; Sulaiman, Safwan; Mokhtar, Mohd Noriznan; Naim, Mohd Nazli; Baharuddin, Azhari Samsu (Faculty of Engineering, Universiti Putra Malaysia, 2016)
Enzyme immobilization is the process of enzyme attachment on solid support that enables repetitive use of enzyme. In this study, kenafbast fibre was bleached with acidified sodium chloriteuntil7 to 13μm in diameter. Then it was functionalized with hexamethylenediamineandglutaraldehyde to form spacer arm and ligand, respectively. Cyclodextringlucanotransferase (CGTase) from Bacillus maceranswas immobilized viacouplinginteraction with ligand onmicrofibre surface. The results show that protein loading and enzyme activity recovery were 27.60% and 21.19%, respectively when 54.196 U/ml of CGTase was used. Besides, storage stability of the immobilized CGTase at 4°C, 25°C and 60°C resulted in 60%, 40% and 15% from its initial activity after 15 days storage. The optimum operating temperature shifted from 60°C to 70°C compared to free CGTase. For reusability study, the immobilized CGTase was able to retain 33% from its initial activity after 7 cycles of batch reaction. Therefore, bleached kenafbast microfibre has high potential to be applied in enzyme immobilization. This can contribute in building sustainable environment as less energy is needed for enzymatic processes in industries. Problems such as effluent disposal and wastage of enzymes can also be eliminated by using the immobilized enzymes developed in this study.